F(X,Xdot) = 0
for steady state using the iteration
[G'] S = -F(X,0)
X += S
G(Y) = F(Y,(Y-X)/dt)
This is linearly-implicit Euler with the residual always evaluated "at steady state". See note below.
|-ts_pseudo_increment <real>||- ratio of increase dt|
|-ts_pseudo_increment_dt_from_initial_dt <truth>||- Increase dt as a ratio from original dt|
Xdot = (Xpredicted - Xold)/dt = (Xold-Xold)/dt = 0
Therefore, the linear system solved by the first Newton iteration is equivalent to the one described above and in the papers. If the user chooses to perform multiple Newton iterations, the algorithm is no longer the one described in the referenced papers.
Index of all TS routines
Table of Contents for all manual pages
Index of all manual pages